Nosocomial Outbreak Due to a Multiresistant Strain of Pseudomonas aeruginosa P12: Efficacy of Cefepime-Amikacin Therapy and Analysis of β-Lactam Resistance - Dubois, Véronique (American Society for Microbiology, 2001)
Over a 3-year period, 67 patients of the Hospital of Pau (Pau, France), including 64 patients hospitalized in the adult intensive care unit (ICU), were colonized and/or infected by strains of Pseudomonas aeruginosa P12, resistant to all potentially active antibiotics except colistin. Most patients were mechanically ventilated and presented respiratory tract infections. Since cefepime and amikacin were the least inactive antibiotics by MIC determination, all ICU patients were treated with this combination, and most of them benefited. Cefepime-amikacin was found highly synergistic in vitro. Ribotyping and arbitrary primer-PCR analysis confirmed the presence of a single clonal isolate. Isoelectrofocusing revealed that the epidemic strain produced large amounts of the chromosomal cephalosporinase and an additional enzyme with a pI of 5.7, corresponding to PSE-1, as demonstrated by PCR and sequencing. Outer membrane protein profiles on sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed the absence of a ca. 46-kDa protein, likely to be OprD, and increased production of two ca. 49- and 50-kDa proteins, consistent with the outer membrane components of the efflux systems, MexAB-OprM and MexEF-OprN. Thus, we report here a nosocomial outbreak due to multiresistant P. aeruginosa P12 exhibiting at least four mechanisms of β-lactam resistance, i.e., production of the penicillinase PSE-1, overproduction of the chromosomal cephalosporinase, loss of OprD, and overexpression of efflux systems, associated with a better activity of cefepime than ceftazidime.